(3eOi JCKjQ GdJLGQI GdEdcJQhfjI aj XGgQI JfGRY GdbhGfjf Pj GdWGHY GdOhdj (B/ s - (3eMeO eMehO Ydj eMehOs; (3YfGjJ YHOGdMejO KGHJs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3jYQV GdHMK debheGJ XGgQI JfGRY GdbhGfjf h HjGf eOi JCKjQ YedjGJ GdJLGQI GdEdcJQhfjI h eSJMOKGJgG aj gPg GdebheGJ (B: (3h deOi SdGeI acQI GdYGde GdEaJQGVj h fJGFLgG ai eLGd JfGRY GdbhGfjf h eOi bHhd GdeSJfO GdEdcJQhfj h GdJhbjY GdEdcJQhfj HOjdjf Yf GdeSJfO GdhQbj h GdJhbjY GdjOhj (B: (3h cPdc eOi JeGKd eTcdGJ GdJLGQI GdEdcJQhfjI PGJ GdWGHY GdOhdj eY eKjdGJgG GdeLQGI HGdhSGFd GdJbdjOjI (B: (3h efgG eTcdI JMOjO ReGf h ecGf GfYbGO GdYbO GdEdcJQhfj (B: (3h OhdjJg (B: (3h eOi EecGf EYeGd bhGYO GdfXGe GdYGe GdhWfj aj ehGLgI GdYedjGJ GdGdcJQhfjI GdeNJdaIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2013 (3, bSe GdbGfhf GdOhdj s
(3HHdjhLQGajG(B: (3UaMGJ (B380-408s
Keywords: (3CSGdjH aV JfGRY GdbhGfjfs; (3GdJLGQI GdEdcJQhfjIs; (3GdSLd GdEdcJQhfj s; (3JfGRY GdbhGfjfs; (3acQI GdYGde GdGaJQGVjs; (3GdYbO GdEdcJQhfjs; (3YedjGJ GdJLGQI GdEdcJQhfjIs; (3GdeSJfO GdEdcJQhfjs; (3GdJhbjY GdEdcJQhfj s; (3bGYOI GdJfGRY s; (3GdbhGYO GdeGOjIs; (3EfchJjQeRs; (3eTGcd GdJLGQI GdEdcJQhfjIs; (3ebOe NOeI GdeYdheGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs